Meningkatkan Kualitas Layanan Melalui Personalisasi Kebutuhan Informasi Pengguna di BATAN - Noer'aida (Perpustakaan IPB, 2019)
With the abundance of information and data, the development of information and communication technology as well as web-based information system applications, has a major influence on library services and user behaviours. In the era of digital libraries, users can obtain the data they need by accessing and managing themselves through Google Scholar, research gate, blog and other media. Libraries at BATAN have provided conventional library services and web-based digital libraries. In order not to be abandoned by users, libraries must provide more personalized and proactive service innovations. To improve service quality, librarians can personalize user needs by recapitulating the most searched keywords through search history or search history on web-based services, namely online cataloguing (OPAC), e-journals, e-repositories, and scientific libraries on portals. management of nuclear knowledge. In addition, user needs can be obtained through the Research and Development Management Information System (SIPL). Librarians collaborate with the SIPL admin in order to download research titles either on an individual basis or per work unit in BATAN in the current year or the coming year. Based on keywords and research titles, librarians make online pathfinder library guides and proactively send the results with complete manuscripts of articles or documents obtained in electronic file form to users via e-mail. It is hoped that the existing portals and applications can be redeveloped in order optimally implement user personalization needs.